\( \overrightarrow{F H} \) bisects \( \angle E F G \). Find the indicated angle measures. \( m \angle G F H=71^{\circ} \). Find \( m \angle E F H \) and \( m \angle E F G \). \( m \angle E F H=\square^{\circ} \) \( m \angle E F G= \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
Since \( \overrightarrow{F H} \) bisects \( \angle E F G \), it divides \( \angle E F G \) into two equal angles, \( \angle E F H \) and \( \angle G F H \). Given that \( m \angle G F H = 71^{\circ} \), we can determine \( m \angle E F H \) as follows: \[ m \angle E F H = m \angle G F H = 71^{\circ} \] Now, to find \( m \angle E F G \), we simply add the measures of the two angles formed by the bisector: \[ m \angle E F G = m \angle E F H + m \angle G F H = 71^{\circ} + 71^{\circ} = 142^{\circ} \] So, the measures are: \( m \angle E F H = 71^{\circ} \) \( m \angle E F G = 142^{\circ} \)